(untitled) (European Journal of Marketing and Economics, 2024)
This research starts from the existing theoretical assumptions that education is a good investment for the employer and positively affects employee satisfaction. Our intention was to test this hypothesis through appropriate research in Serbia and to identify which factors and to what extent it influences.We started from the fact that HR is a complex process and influenced by various factors. In this context, special attention is paid to the integration of training and education into other HR processes, as one of the most important conditions for influencing business results and employee satisfaction. In doing so, it is especially true that the HRM concept in Serbia has been accepted with great delay and only with the arrival of foreign investors.The main goal of this research is to identify and examine the factors that influence the effects of training/education in the organizational context, and to determine under what conditions education can be an investment rather than an expense. This work is methodologically based on the analysis of the available literature and the results of the research of the authors statistically processed based on the survey on the example of -187 respondents from companies selected by random sample. An appropriate model is presented that in a simple way shows the factors influencing the cost-effectiveness of investment in education/ training.